Geographic Distribution of Natural Products Produced by the Red Alga Laurencia dendroidea J. Agardh. Issue 7 (24th June 2016) - Machado, Fernanda L. S.; Duarte, Heitor M.; Gestinari, Lísia M. S.; Cassano, Valéria; Kaiser, Carlos R.; Soares, Angélica R.
Abstract : In order to evaluate the chemical diversity of Laurencia dendroidea J.Agardh, a widely distributed seaweed in Brazilian coast, a phytochemical study was carried out with algae collected from six different locations along the Southeast Brazilian coast. Purified compounds were identified by MS and NMR techniques. The chemical profiles of lipophilic extracts were obtained by GC/MS for each population. In total, 15 compounds were described. The sesquiterpene composition accounted for 49 – 63% of the GC/MS chromatogram area. The discrimination of three chemotypes was done by the use of HCA on GC/MS chromatograms. They were also analyzed by the PCA and, together with peak area analysis, it was possible to discriminate all populations by the main variation of elatol, obtusol, rogiolol, and triquinane. The results revealed the high diversity of sesquiterpene composition among populations of L. dendroidea . Curiously, the within and among population variation of elatol and obtusol suggested a biochemical interplay on the content of these compounds. More studies are necessary to understand the patterns of chemical diversity and compound variation within and among populations of L. dendroidea .